The Stability and Validity of Automated Indices of Vocal Development in Infants With Autistic and Non-Autistic Siblings. - Markfeld, Jennifer E.; Feldman, Jacob I.; Daly, Claire; Santapuram, Pooja; Bowman, Sarah M.; Dunham-Carr, Kacie; Suzman, Evan; Keçeli-Kaysılı, Bahar; Woynaroski, Tiffany G. (Journal of Speech, Language & Hearing Research, 2023)
Purpose: This study evaluates the extent to which automated indices of vocal development are stable and valid for predicting language in infants at increased familial likelihood for autism and/or language impairment and relatively lower likelihood infants. Method: A group of infants with autistic siblings (Sibs-autism; 20 infants) and a comparison group of infants with non-autistic siblings (Sibs-NA; 20 infants) wore Language ENvironment Analysis (LENA) recording devices for 16 hr on 2 days within a 1-week period. Extant software was used to derive several putative indices of vocal development from these recordings. Stability of these variables was examined across and within groups. Expressive and receptive language aggregates were calculated for each participant. Multiple regression analyses were used to (a) evaluate zero-order correlations for variables derived from LENA recordings with concurrent and future language and (b) test whether those associations were moderated by group status. Results: Both stability and validity differed by variable and group status. All variables reached acceptable stability in the Sibs-autism group within two to three observations, whereas stability of most variables was attenuated in the Sibs-NA group. No variables were associated with concurrent language in the theoretically motivated direction across groups, but two variables were strongly associated with concurrent expressive language in only the Sibs-NA group. Additionally, two variables were associated with later expressive language, though these correlations were again stronger in the Sibs-NA versus Sibs-autism group. Conclusions: Although selected automated indices of vocal development were stable in Sibs-autism and/or valid for predicting expressive language within Sibs-NA, no scores showed strong, theoretically motivated associations with language within the Sibs-autism group. Automated indices of vocal development may, thus, have limited validity or clinical utility for predicting language development in infants at elevated familial likelihood for autism. Supplemental Material: https://doi.org/10.23641/asha.24415735